Effect of organic farming on soil erosion and soil structure of reclaimed Tepetates in Tlaxcala, Mexico - Haulon, Mathieu; Justus Liebig University Giessen (My University, 2008)
"Tepetates" are hardened layers in the profile of soils from volcanic origin. After erosion of the overlying soil horizon, the tepetates show up on the surface. In the Mexican highlands, along the Trans-Mexican Volcanic Belt, this phenomenon has caused the emergence of vast degraded and sterile areas. The State of Tlaxcala is one of the most affected, with 15 % of theState area covered by bare tepetates. The rehabilitation of tepetates is a way to increase arable lands and mitigate environmental impact caused by high superficial runoff. Previous research experiences showed that soil erosion control is critical to achieve sustainable tepetates rehabilitation. The application of organic amendments have been repeatedly recommended to increase fertility and soil physical properties after fragmentation, but there islittle data available on the effect of organic farming on soil erosion during the rehabilitation process. The aim of this research is to evaluate the effect of organic farming on soil erosion and soil structure at field scale and under natural conditions. A four years experiment was set up in Tlaxcala, Mexico. Erosion and runoff rates were measured in five terraced plots of 580 to 2200 m2 and with 3-4 % slope. Three plots were fragmented in 1986 and two in 2002. Three farming managements were compared: The "conventional", with mineral fertilization and no incorporation of O.M.; the "improved", withmineral fertilization and incorporation of crop residues, and the "organic" with organic fertilization. Soil structure was assessed by total porosity, pore size distribution and aggregate stability. Annual precipitation ranged between 507 mm in 2005 to 805 mm in 2003, with annual erosivity of 195 N h-1 and 345 N h-1 respectively. In plots reclaimed in 2002, soil loss ranged from 8.6 to 19.1 t ha-1 yr-1 under conventional management and from 5.5 to 14.1 t ha-1 yr-1under organic farming. In plots reclaimed in 1986 soil loss ranged from 1.1 to 5.6 t ha-1 yr-1with no significant difference between managements. The incorporation of fresh organicmatter in organic farming provided short term increase in aggregates stability, regardless ofthe age of rehabilitation. However, aggregate stability was not significantly correlated to SOCnor to erosion rates. Multiple regression analysis showed that for annual values, SOC is themain factor controlling erosion rates in reclaimed tepetates, explaining 64 % of soil lossvariance and 79 % of runoff variance. The evolution of erosion rates is therefore dependanton carbon accumulation rates. After fragmentation, organic farming increased carbon sequestration rate to 0.8 Mg C ha-1 yr-1 compared to 0.22 Mg C ha-1 yr-1 in conventional management. In plots reclaimed in 1986,carbon sequestration ranged from 0.21 Mg C ha-1 yr-1 in conventional management to 0.37Mg C ha-1 yr-1 in improved management and 0.61 Mg C ha-1 yr-1 in organic management.Erosion rates in terraced reclaimed tepetates could decrease below tolerable value (< 10 t ha-1yr-1) three years after fragmentation under organic farming, compared to seven years underconventional farming. Results also confirmed the key role played by vegetation cover (accounting for 27 % of soilloss variance for single events) and emphasize the importance of crop nutrition and cropassociation to control erosion. Improved management provided Total porosity ranged from 44.8 % on average in 2003 to 50.4 % on average in 2005. Weobserved no significant effect of management or age of rehabilitation on soil porosity andpore size distribution, suggesting that high tillage intensity during the cropping season whichprevented significant changes in porosity between managements. This three years study demonstrated that organic farming has a positive effect on soil erosionduring rehabilitation of tepetates. However, unless a market for organic products is developedand a certification system established, we recommend organic amendments to becomplemented with mineral fertilization to ensure optimum vegetation cover and erosioncontrol.
Keywords: ddc:630